دراسة الأثر البيئي على المباني الترفيهية معمارياً وعمرانياً - أومري أديب داري (Latakia University Journal -Engineering Sciences Series, 2016)
إن الثقافة البيئية غالباً ما تكون غائبة عن أذهان المستثمرين ولا تقع في دائرة اهتمامهم ومن ثَمَّ كرس المعماري جهوده في مجال إنتاج الشكل، دون النظر إلى مدى تأثره بمفاهيم الاستدامة فضلاً عن تأثير إنتاجه على البيئة بشكل سلبي،فنجد منتجات معمارية تحتاج إلى تكاليف تشغيل عالية نظراً للمبالغة في استعمال مواد قد لا تكون متوافقة بيئياً ،والمعماري وحده ليس مسؤولاً ، فهناك أيضاً عدم تقدير من المجتمع أو اهتمام بالمدخل التقليدي في العمارة(استعمال حلول تقليدية في معالجة المناخ) إضافة إلى عدم وجود من يردعه عبر تشريعات بيئية حقيقية. لذا لابد من اتخاذ إجراءات بيئية ملزمة للمباني والمجمعات السياحية القائمة، والتقيد بدراسة معايير بيئية ضرورية للوصول لسياحة بيئية تحترم البيئة ،وتخفض من استهلاك الموارد وذلك على مستوى العملية التصميمية وعلى مستوى السياحة المستدامة. يرصد البحث هذه العملية، ويعرض الخطوات الأساسة التي يجب أن تتبع في حل مثل هذه المنشآت وذلك عن طريق الرصد لبعض المنشآت الترفيهية والمجمعات السياحية حول العالم، وشرح المؤثرات العامة التي أدت إلى تطور هذا النوع من المنشآت، كما يتضمن وضع بعض الأسس والمبادئ والمعايير العامة لضبط العملية التصميمية معمارياً و تخطيطياً، وذلك للتصدي لمثل هذه الأبنية أكاديمياً في سورية. The environmental culture is often absent from the minds of investors. Thus, devoted architect efforts in the field of production form،Without regard to the extent influenced by the concepts of sustainability. As well as the impact of production on the environment negatively. We find architectural products require high operating costs. Because of exaggeration in the use of materials may not be environmentally compatible. The architect alone is not responsible. There is also a lack of appreciation from the community. Or interest in the traditional entrance in Architecture, (Use of traditional solutions in climate treatment( In addition to the lack of real environmental legislation to deter it. It is imperative to make binding for buildings and tourist complexes existing environmental procedures. And adherence to the study is necessary to reach the tourism respectful of the environmental standards. Reduction of the consumption of resources and on the design process and the level of sustainable tourism level. This paper deals with the process and presents the basic steps that you must follow in resolving such buildings. And through monitoring some recreational facilities and tourist complexes around the world. It explains the general effects that led to the development of this type of buildings. It also includes some of the foundations and the general principles and standards-setting process to adjust the design and architectural sketch. In order to address such buildings academically in Syria.